Escalating EFL Collaborative Writing Culture through the Use of Google Docs - Wijaya, Kristian Florensio (Universitas Pelita Harapan, 2024)
Since EFL writing learning enterprises are frequently regarded as single-handedly activities, collaborative writing culture plays a crucial role in increasing globalized EFL learners’ writing motivation leading them to become more optimistic, innovative, and proficient writers. This current small-scale library study was projected to profoundly investigate whether EFL collaborative writing culture can thrive in the support of Google Docs. Accordingly, the researcher critically reviewed the foregoing research results yielded by 20 previously published collaborative writing and Google Docs studies with the accompaniment of a thematic analysis. A thematic analysis approach was incorporated to ascertain the credibility, believability, and reliability of each specifically clustered research result. To produce more relatable and contextual research results, the researcher selected prior collaborative writing and Google Docs investigations ranging from 2019 until 2023 year. In conformance with the particularly obtained research results, second language writing instructors all around the globe are strongly suggested to fuse the further internalization of collaborative writing strategy with Google Docs to constantly transform EFL learners into more collaborative, resilient, persistent, and life-long writers. Bahasa Indonesia Abstrak Berkenaan dengan fakta bahwa pembelajaran penulisan Bahasa Inggris sering dianggap sebagai aktivitas individual, budaya menulis kolaboratif memegang sebuah peranan penting untuk meningkatkan motivasi menulis pelajar Bahasa Inggris di seluruh dunia yang dapat membawa mereka menjadi penulis optimis, inovatif, dan cakap. Studi pustaka skala kecil ini diperuntukan secara mendalam untuk menyelidiki apakah budaya menulis kolaboratif dapat tumbuh dengan dukungan Google Docs. Oleh karena itu, peneliti dengan sangat kritis meninjau hasil penelitian yang telah dihasilkan oleh 20 penelitian menulis kolaboratif dan Google Docs dengan bantuan dari analisis tematik. Metode analisis tematik diterapkan untuk memastikan kredibilitas, kepercayaan, dan keandalan dari setiap hasil penelitian yang telah dikelompokan secara spesifik. Untuk menghasilan hasil penelitian yang relevan dan kontekstual, peneliti memilih penelitian menulis kolaboratif dan Google Docs dari tahun 2019 hingga 2023. Berkenaan dengan hasil penelitian yang telah didapat, instruktur menulis Bahasa Inggris di seluruh dunia disarankan untuk menggabungkan penerapan strategi menulis kolaboratif dengan Google Docs agar secara terus menerus mentransformasi pelajar Bahasa Inggris menjadi penulis seumur hidup yang lebih kolaboratif, tangguh, dan ulet.